Frequency of hospital readmissions for venous thromboembolism and associated hospital costs and length of stay among acute medically ill patients in the US. (2nd November 2019) - Amin, Alpesh; Deitelzweig, Steven; Bucior, Iwona; Lin, Jay; Lingohr-Smith, Melissa; Menges, Brandy; Neuman, W. Richey
Abstract: Objectives: This study evaluated the frequency of hospital readmissions for venous thromboembolism (VTE) and the associated costs and length of stay (LOS) among acute medically ill patients in the US using a real-world claims database analysis. Methods: Patients (≥40 years of age) at risk of VTE due to hospitalization for acute medical illnesses, based on primary hospital discharge diagnosis codes, were identified from the MarketScan databases between July 1, 2011 and March 31, 2015. Patients were required to have continuous insurance enrollment in the 6 months prior to initial (index) hospitalizations (baseline period) and in the 6 months after hospital discharge (follow-up period). The proportions of patients with VTE-related (diagnosis at any position) and VTE as primary diagnosis hospital readmissions during the follow-up period were evaluated. The associated costs and LOS for such readmissions were also determined, as well as time to VTE-related readmissions. Results: Of the study population ( n = 12, 785; mean age = 68.3 years), most were hospitalized primarily for infectious diseases (35.2%), followed by respiratory diseases (27.9%), cancer (15.7%), heart failure (11.8%), ischemic stroke (8.1%), and rheumatic diseases (1.4%). Of the overall study population, 2.1% ( n = 268) had a VTE-related hospital readmission in the 6 months following discharge of their index hospitalization, of which 36.6% ( n = 98) were for a primary diagnosis of VTE. Approximately 25.4% of the VTE-related hospital readmissions occurred within the first 30 days of discharge and 58.2% within 90 days. The mean cost for a hospital readmission with a primary diagnosis of VTE was 18, 681 (mean LOS = 5.0 days); for readmissions with a primary diagnosis of DVT and PE, mean costs were 14, 719 and 23, 305, respectively. Conclusions: Among this study population of patients hospitalized for acute medical illnesses, some experienced a VTE event requiring re-hospitalization, with 25% occurring within the first 30 days after hospital discharge.